Enhancing brand communication effectiveness through social media in student recruitment at Binh Duong University - Danh, Phi Phụng; Le, Hoàng Trân; Nguyen, Thị Hồng Phượng; Vo, Thị Thanh Nga (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The rapid development of universities in Vietnam has created numerous challenges, particularly in improving education quality and competition among institutions. This paper focuses on analyzing the communication strategy situation at Binh Duong University. Based on this analysis, the research team proposes several solutions to enhance the effectiveness of the communication strategy to attract students through social media platforms.